Cardiovascular disturbances and atherosclerosis risk Гасtore in systemic lupus erythematosus - T V Popkova; Z S Alekberova; E N Aleksandrova; O V Bulgakova; E L Nassonov (Научно-практическая ревматология)
Objective. To assess frequency and significance of atherosclerosis and connected with it cardiovascular disturbances (CVD) risk factors in pts wilh systemic lupus erythematosus (SLE). Material and methods. 99 pts (mean age 35,9± 10,8 years, mean disease duration 106± 115,5 months) were examined. Classical risk factors were analyzed. Coronary complications risk was assessed with "Scheme of individual total (general) coronary heart disease (CHD) clinical signs risk determination”. Duplex scanning of common carotid arteries was performed. C-reactive protein (CRP) was evaluated by high-sensitivity immune-enzyme assay with Bender MedSystems commercial kits. Results. 92% of SLE pts had at least one classical atherosclerosis risk factor, most often - dislipidemia (DLP) or hypertension (HT). Subclinical atherosclerosis signs characterized by increase of intima-media complex thickness and DLP were more frequent in pts with HT than without HT (p=0,00l and p=0,008 respectively. Total CHD clinical signs risk in group with atherosclerosis features was higher than in group of pts without atherosclerosis (p=0,0001).A positive correlation between total risk of coronary complications and CRP concentration (r=0,27, p=0,02). Conclusion. Classical and some "ersatz" risk factors are of considerable significance in atherosclerosis and connected with it CVD progression. Multiple-factor analysis of different indices and evaluation of their role in the CVD development in SLE pts are essential for examination of mechanisms of early atherosclerosis development.